Penggunaan Istilah Psikologi Arab dalam Mu'jam Mustakhalahats 'Ilm Nafsi untuk Pengayaan Konsep Psikologi Indonesia - Rizky, Muhammad Wahyu; Ulil Abshar; Darsita Suparno; Achmad Satori; Zam Zam Nurhuda; Achmad Hifni (IAIN Madura, 2023)
The purpose of this study is to provide an overview of the use of Arabic psychological terms originating from Mu'jam mustakhalahats 'ilm nafsi for the development of Indonesian psychological terms through the translation process. In this study, the authors used a descriptive qualitative method by collecting data in the form of psychological vocabulary, recording and collecting psychological vocabulary, analyzing psychological vocabulary, and then finally providing explanations and analysis using Abdul Chaer's morphological theory. The results of the study show that the use of Arabic psychological terms in Mu'jam Mustakhalahats 'Ilm Nafsi has relevance in the context of the development of psychological concepts in Indonesia. By understanding these terms, psychologists in Indonesia can enrich aspects of theoretical and practical understanding, as well as develop an inclusive and comprehensive approach in understanding and explaining psychological, social and cultural phenomena in Indonesian society.